Bayesian Estimation Using Progressively Censored Masked Data Under Asymmetric Loss Function - Tomer, S.K.; Kumar, Jitendra (Journal of Institute of Science and Technology, 2015)
Competing risk modeling is very useful for the assessment of component characteristics in reliability studies. In this paper, we consider the competing risk modeling of progressively censored data when units under lifetest are series system of two components. Assuming the lifetime distributions of components to be exponentially distributed, we obtain Bayes estimate of parameters and components relative risks under asymmetric loss functions. Bayesian computation is done using Lindley’s approximation. A simulation study is presented for numerical illustrations. Journal of Institute of Science and Technology, 2015, 20(1): 40-50